THE EFFECT OF TRUST, PERCEPTION OF RISK AND SECURITY ON CONSUMER PURCHASE INTEREST IN LAZADA (EMPIRICAL STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, IBN SINA UNIVERSITY) - M. Arpah; Maizar; Septa Diana Nabella (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study supposed to determine the effect of trust, risk perception and security on consumer buying interest at Lazada. The type of research in this study is causality research, namely research that is structured to examine the possibility of a causal relationship between variables with a survey method. The population in this study were active students at the Faculty of Economics and Business, Ibn Sina University, totaling 1,679 people. The sample criteria used in this study were at least one purchase at Lazada. The sampling technique used in this study was simple random sampling with a sample size of 95 respondents. The instruments used in this study are observation guidelines, interview guidelines and questionnaire guidelines. Research instruments are supported by primary data and secondary data. The data analysis technique used uses Validity Test and Reliability Test then clasic assumption test, multiple regression test and hypothesis testing including t test f test and determination test. The results of this study are partially the Trust variable has a positive and significant effect on Lazada consumer buying interest, where the t count of trust is 8.346> 1.986 t table and the sig value is 0.000 <0.05. Risk perception variables have a positive and significant effect on consumer buying interest in Lazada, where the t count for risk perception is 3.675> 1.986 t table and sig value is 0.003 <0.05. Security variables have a positive and significant effect on Lazada consumer buying interest, where the t count for security is 2.466> 1.986 t table and sig value is 0.001 <0.05. The results of the study simultaneously are trust, risk perception and security simultaneously have a positive and significant effect on consumer buying interest in Lazada with F count of 82.246> 2.70 F table and a significance of 0.000 <0.05.